Contribution Des Femmes A La Production Piscicole En Côte D’Ivoire - Anoumou Hortense Yao; Ahou Rachel Koumi; Boua Célestin Atsé; Essetchi Paul Kouamelan (European Scientific Journal, ESJ, 2016)
Women play a major role in the accession to food security because of their significant contribution to agriculture. However, very few data exists on women’s contribution to the Cote d’Ivoire fish production. The objective of this study was to evaluate the ability of fish farms owned by women to contribute to the fish production in Cote d'Ivoire. A survey has been conducted on women fish farms characteristics and their production capacity. Only 5.98% of 301 farms belonged to women with a contribution to the total production of 2.89%. They are mostly farmers (44.44%) aged 30 to 60 years (88.89%), native of the regions (66.67%) where they had their farms. Tilapia and catfish are the main species produced with a semi-intensive (83.33%) farming system in pond. The area of production is less than 1 hectare (77.78%). Commercial or farms-made feeds are preferably used as fish feeds. Women-owned farms production is characterized by the tilapia commercial weigh over 300 g (66.67%) and a yield of 1000 kg/ha/year (77.78%). By their choice of production system, feeds and their production capacity, women can contribute to set up a sustainable production environment of farm fish in Cote d'Ivoire.